Rämpätirää. - Betoniporsas; Kautto, Iiro; Niiva, Esa, 1965-; Peippo, Henrikki; Väisänen, Jukka; Lindström, Timo, 1948-2022; Pikkarainen, Hannu; Luukkanen, Timo; Warner Music Finland ([Espoo] : Warner Music Finland, 1998)
12 kappaletta.
Laulujen sanat tekstiliitteessä.
Laulujen sanat tekstilipukkeessa.
Betoniporsas: Esa Niiva (sax, hca, b-cl), Iiro Kautto (b), Henrikki Peippo (dr, perc), Jukka Väisänen (p, acc), Timo Luukkanen (voc, g).
Sanat tekstiliitteessä: suomi.
Keywords: lastenlaulut